2017
DOI: 10.1002/reg2.88
|View full text |Cite
|
Sign up to set email alerts
|

Impaired caudal fin‐fold regeneration in zebrafish deficient for the tumor suppressor Pten

Abstract: Zebrafish are able to completely regrow their caudal fin‐folds after amputation. Following injury, wound healing occurs, followed by the formation of a blastema, which produces cells to replace the lost tissue in the final phase of regenerative outgrowth. Here we show that, surprisingly, the phosphatase and tumor suppressor Pten, an antagonist of phosphoinositide‐3‐kinase (PI3K) signaling, is required for zebrafish caudal fin‐fold regeneration. We found that homozygous knock‐out mutant (ptena−/−ptenb−/−) zebra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…22 Disruption in any of these pathways could adversely alter the regenerative capacity of zebrafish caudal fin. [40][41][42] Based on our data, we propose that basp1 regulates revascularization through the Wnt/β-catenin pathway and accompanied pathways such as notch signaling. Further studies to elucidate how BASP1 modulates CXXC4, an epigenetic silencer of the β-catenin gene, expression will provide valuable new information in understanding the direct role of BASP1 in angiogenic responsiveness.…”
Section: F I G U R Ementioning
confidence: 94%
“…22 Disruption in any of these pathways could adversely alter the regenerative capacity of zebrafish caudal fin. [40][41][42] Based on our data, we propose that basp1 regulates revascularization through the Wnt/β-catenin pathway and accompanied pathways such as notch signaling. Further studies to elucidate how BASP1 modulates CXXC4, an epigenetic silencer of the β-catenin gene, expression will provide valuable new information in understanding the direct role of BASP1 in angiogenic responsiveness.…”
Section: F I G U R Ementioning
confidence: 94%
“…Another miRNA, miR-21, could decrease autophagy by down-regulating PTEN in mesangial cells [ 37 ]. In fish, it has been reported that zebrafish PTEN deficiency induced the activation of PI3K/mTOR pathway and AKT, which affected embryo and tissue development [ 38 , 41 ]; madaka PTEN knockout also upregulated PI3K/AKT signaling, which led to abnormal embryo development [ 42 ]. In the present study, we found that compared with human and mouse PTEN, fish PTEN homologs are highly conserved in sequence and structure, and, in flounder, PoPTEN was constitutively expressed in a wide range of tissues.…”
Section: Discussionmentioning
confidence: 99%
“…In mammals, it has been demonstrated that miRNAs regulate cell apoptosis, proliferation, and autophagy by targeting PTEN [ 35 , 36 , 37 ]. In fish, studies on PTEN have been documented mainly in zebrafish, in which it was shown that PTEN played an important role in embryonic development, caudal fin-fold regeneration, tumorigenesis, hematopoiesis, and myelocyte migration [ 38 , 39 , 40 , 41 ]. In medaka, PTEN was also shown to be involved in embryo development [ 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…One study conducted by the Jazwinska group revealed that the activity of bone morphogenetic protein (BMP) is responsible for WE maintenance and osteoblast and blood vessel formation (Thorimbert et al, 2015). Moreover, it has been observed that the phosphatase and tumor suppressor Pten, which is an antagonist of phosphoinositide-3-kinase (PI3K) signaling, is required for caudal fin fold regeneration in zebrafish larvae (Hale et al, 2017). A recent study found that homozygous knockout mutant zebrafish embryos lacking functional Pten (ptena −/− ptenb −/− ) were not capable of regenerating their caudal fin folds.…”
Section: Zebrafish and Tail Fin Regenerationmentioning
confidence: 99%
“…These organisms showed decreased proliferation and enhanced apoptotic activity. The reinduction of Pten expression or pharmacological inhibition of PI3K, in turn, rescued the regenerative process (Hale et al, 2017). In addition to proliferative cells from the blastema, several studies have shown that macrophages play an important role in regenerative processes through protein synthesis, angiogenesis, the production and release of cytokines such as VEGF and interleukin 1 (IL-1), and the promotion of cell proliferation (Koh and DiPietro, 2011; Wynn and Vannella, 2016; Godwin et al, 2017; Abnave and Ghigo, 2018).…”
Section: Zebrafish and Tail Fin Regenerationmentioning
confidence: 99%